STATIN trial: predictive performance of competing‐risks model in screening for pre‐eclampsia at 35–37 weeks' gestation. (5th January 2022) - Döbert, M.; Wright, A.; Varouxaki, A. N.; Mu, A. C.; Syngelaki, A.; Rehal, A.; Delgado, J. L.; Akolekar, R.; Muscettola, G.; Janga, D.; Singh, M.; Martin‐Alonso, R.; et al.
ABSTRACT: Objective: To examine the predictive performance of a previously reported competing‐risks model of screening for pre‐eclampsia (PE) at 35–37 weeks' gestation by combinations of maternal risk factors, mean arterial pressure (MAP), uterine artery pulsatility index (UtA‐PI), serum placental growth factor (PlGF) and serum soluble fms‐like tyrosine kinase‐1 (sFlt‐1) in a validation dataset derived from the screened population of the STATIN study. Methods: This was a prospective third‐trimester multicenter study of screening for PE in singleton pregnancies by means of a previously reported algorithm that combines maternal risk factors and biomarkers. Women in the high‐risk group were invited to participate in a trial of pravastatin vs placebo, but the trial showed no evidence of an effect of pravastatin in the prevention of PE. Patient‐specific risks of delivery with PE were calculated using the competing‐risks model, and the performance of screening for PE by maternal risk factors alone and by various combinations of risk factors with MAP, UtA‐PI, PlGF and sFlt‐1 was assessed. The predictive performance of the model was examined by, first, the ability of the model to discriminate between the PE and no‐PE groups using the area under the receiver‐operating‐characteristics curve (AUC) and the detection rate at a fixed false‐positive rate of 10%, and, second, calibration by measurements of calibration slope and calibration‐in‐the‐large. Results: The study population of 29 677 pregnancies contained 653 that developed PE. In screening for PE by a combination of maternal risk factors, MAP, PlGF and sFlt‐1 (triple test), the detection rate at a 10% false‐positive rate was 79% (95% CI, 76–82%) and the results were consistent with the data used for developing the algorithm. Addition of UtA‐PI did not improve the prediction provided by the triple test. The AUC for the triple test was 0.923 (95% CI, 0.913–0.932), demonstrating very high discrimination between affected and unaffected pregnancies. Similarly, the calibration slope was 0.875 (95% CI, 0.831–0.919), demonstrating good agreement between the predicted risk and observed incidence of PE. Conclusion: The competing‐risks model provides an effective and reproducible method for third‐trimester prediction of term PE. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.